(untitled) (Medico Legal Update, 2021)
Health insurance is a type of insurance product that specifically guarantees the cost of health or care of the insurance members if they are sick or have an accident. Implementation of social security is a state obligation mandated by the 1945 Constitution. The issuance of the Social Insurance Management Agency (BPJS) act as the implementer of the National Social Security System act (SJSN) resulted in PT Askes transforming into Social Insurance Management Agency on Health (BPJS Kesehatan). The National Social Security System is organized on the basis of humanitarian principles, principles of benefit, and the principle of social justice for all Indonesians. The National Social Security System aims to provide and guarantees the fulfillment of a decent life base for each participant and/or his family member. The National Social Security System is organized on the basis of such principles: mutual cooperation, non-profit, disclosure, prudence, accountability, portability, mandatory membership, trust fund, and the social security fund will be used entirely for program development and for the interest of participants. Although the preparation and implementation of the National Social Security System is quite well, but in reality there are still various impacts and problems encountered in the operation of BPJS Kesehatan such as lack of socialization, service facilities, inappropriate data, and personnel who are still lacking in giving a good services and information.